A review of the factors associated with the non‐use of respite services by carers of people with dementia: implications for policy and practice. (27th March 2013) - Phillipson, Lyn; Jones, Sandra C.; Magee, Christopher
Abstract The use of respite services by carers has been shown to extend the length of time people with dementia can remain living in the community with family support. However, the use of respite services by informal carers of people with dementia is often low and does not appear to match carer need. To better understand how to address carers' unmet need for respite, the factors that impede respite service use must be identified. To achieve this, a narrative synthesis of published academic literature (1990–2011) was undertaken regarding factors associated with not utilising different types of respite services utilising Anderson's Behavioural Model of Service Use. The review reinforces the importance of the assessment and matching of services to the needs of individual carers and care recipients at the local level. It also highlights the need to move beyond care pathways for individuals. To support respite use there is a need for local action to be augmented at a community or population level by strategies to address attitudinal and resource barriers that influence sub‐groups of the carer population who may be more vulnerable to service non‐use.